Towards a generic procedure for the detection of relevant contaminants from waste electric and electronic equipment (WEEE) in plastic food-contact materials: a review and selection of key parameters - Puype, Franky; Samsonek, Jiří; Vilímková, Věra; Kopečková, Šárka; Ratiborská, Andrea; Knoop, Jan; Egelkraut-Holtus, Marion; Ortlieb, Markus; Oppermann, Uwe (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2017)
Recently, traces of brominated flame retardants (BFRs) have been detected in black plastic food-contact materials (FCMs), indicating the presence of recycled plastics, mainly coming from waste electric and electronic equipment (WEEE) as BFRs are one of the main additives in electric applications. In order to evaluate efficiently and preliminary in situ the presence of WEEE in plastic FCMs, a generic procedure for the evaluation of WEEE presence in plastic FCMs by using defined parameters having each an associated importance level has been proposed. This can be achieved by combining parameters like overall bromine (Br) and antimony (Sb) content; additive and reactive BFR, rare earth element (REE) and WEEE-relevant elemental content and additionally polymer purity. In most of the cases, the WEEE contamination could be confirmed by combining X-ray fluorescence (XRF) spectrometry and thermal desorption/pyrolysis gas chromatography-mass spectrometry (GC-MS) at first. The Sb and REE content did not give a full confirmation as to the source of contamination, however for Sb the opposite counts: Sb was joined with elevated Br signals. Therefore, Br at first followed by Sb were used as WEEE precursors as both elements are used as synergetic flame-retardant systems. WEEE-specific REEs could be used for small WEEE (sWEEE) confirmation; however, this parameter should be interpreted with care. The polymer purity by Fourier-transform infrared spectrometer (FTIR) and pyrolysis GC-MS in many cases could not confirm WEEE-specific contamination; however, it can be used for purity measurements and for the suspicion of the usage of recycled fractions (WEEE and non-WEEE) as a third-line confirmation. To the best of our knowledge, the addition of WEEE waste to plastic FCMs is illegal; however, due to lack on screening mechanisms, there is still the breakthrough of such articles onto the market, and, therefore, our generic procedure enables the quick and effective screening of suspicious samples.
Keywords: waste electric and electronic equipment; pyrolysis mass spectrometry; brominated flame retardants; food-contact materials; retardanty hoření; X-ray fluorescence spectroscopy; Plastics; plastické hmoty; obaly potravin; Recycling; Flame Retardants; Bromine; brom; Inductively coupled plasma optical emission spectroscopy; Food Packaging; attenuated total reflectance Fourier-transformed infrared spectroscopy; recyklace; plynová chromatografie s hmotnostně spektrometrickou detekcí; elektronický odpad; Gas Chromatography-Mass Spectrometry; thermal desorption; rare earth elements; Electronic Waste